Ensino da narrativa no 5.º ano do Ensino Fundamental: caminhos para resiliência, cuidado de si e do outro, superação de conflitos e acesso à vida social - Cotta, Valdirene Aparecida (2021)
In this master thesis, we present theoretical reflections and didactic propositions related to canonical narratives as a path to resilience, care for oneself and the other, overcoming of conflicts and access to social life, given its ability to contribute to human development. The general objective of research was to provide students with reflections on the process of reading and creating narratives to increase resilience and the ability to face life’s obstacles based on experiences and on the multiple processes of access to reading and writing. It is a qualitative interpretive research, in which we use the methods of bibliographic research to review the literature, and of action research, through the technique of observation, elaboration and application of a Didactic Unit addressing the teaching of narratives to the 5th year of Elementary School. Our theoretical framework is mainly based on the method of analysis of narratives through the generative path of signification, according to Greimas’ narrative semiotics. To support our discussion and the development of the didactic unit, we rely mainly on the works by Greimas (1973-2014), Fiorin (2003-2011), Bruner (2001-2002) and Grandesso (2000), among other authors. Based on the theoretical reflections and the application of activities to students, we analyzed the results, which show that the strategies used in the classes favored the understanding of canonical narratives from the perspective announced in the research objective. The students understood that oral and written narrative expressions interfere in the subjects’ lives and allow them to express their way of thinking, their feelings, emotions and knowledge, and thus the narratives can contribute effectively to the social, cultural and cognitive education.